The english teaching techniques and its relation to the meaninful learning with students of 1st, 2nd and 3rd years of high school curriculum at “27 de Febrero” high school. Academic year 2008-2009 - Carrion, Adela Marlene (2010)
The present research work entitled, “TEACHING TECHNIQUES AND ITS RELATION TO THE MEANINFUL LEARNING WITH STUDENTS OF 1ST, 2ND AND 3RD YEARS OF HIGH SCHOOL CURRICULUM AT “27 DE FEBRERO” HIGH SCHOOL. ACADEMIC YEAR 2008-2009.” has been developed with the purpose to contribute to the quality of the English teaching –learning process that is carried out at researched high school by means of this study. To carry out this research work we applied the instrument of the survey which was applied as to the teachers as well to the students and to process the information we used the inductive – deductive, analytic synthetic methods and the elaboration of the final report the descriptive method. The obtained results show us that most of teachers do not apply suitable techniques to develop the receptive skills neither they make students to practice extensive listening and reading, which is necessary to get meaningful learning with the students. Speaking and writing skills are developed through the book exercises which is not enough to get meaningful learning with the in accuracy and fluency. On the other hand, teachers do not motivate students to learn the English language which requires the application of appropriate techniques to encourage the students to be involved in the learning process To sum up, we can say the teaching techniques applied by teachers at “27 de Febrero” High School are not getting meaningful learning in the English language with the students of 1st, 2nd and 3rd years of high School Curriculum at “27 de Febrero” High School. Academic Period 2008-2009.